Effectiveness of Reproductive Biology Educational Interventions in Reducing the Prevalence of Elective Caesarean Sections - Novita; Achmarina Chusban; Susi Indriani; Vera Widiastuti; Valeena Alberthini; Warastuti; Reza Mareta Ramadona; Badariah (Postgraduate, University of Mataram, 2024)
Indonesia has the highest caesarean section rate globally, with a prevalence of 17.6% in 2018, rising to 22.50% among urban women by 2021, far exceeding the WHO recommendation of 10-15%. Although caesarean sections can be life-saving, they carry higher risks of complications for both mother and baby compared to normal delivery. This study aims to evaluate the impact of reproductive biology educational interventions on reducing elective caesarean sections at Aulia Pandeglang Regional Hospital in Banten in 2024. Utilizing a quasi-experimental design with a One Group Pre and Post Test approach, the research shows that such educational interventions significantly lower elective caesarean rates. Pre-test data revealed that 70% of cases were in the medium category, while post-test data showed a reduction to 43% in the low category. All respondents participated in both pre-test and post-test evaluations. The findings strongly support the effectiveness of reproductive biology education in decreasing elective caesarean sections, prompting Aulia Pandeglang Regional Hospital to continue its educational program for pregnant women to promote normal delivery.